2016
DOI: 10.1159/000448941
|View full text |Cite
|
Sign up to set email alerts
|

Doxapram Treatment for Apnea of Prematurity: A Systematic Review

Abstract: Background: Apnea of prematurity (AOP) is a common complication of preterm birth, for which caffeine is the first treatment of choice. In case of persistent AOP, doxapram has been advocated as an additional therapy. Objective: To identify and appraise all existing evidence regarding efficacy and safety of doxapram use for AOP in infants born before 34 weeks of gestational age. Methods: All studies reporting on doxapram use for AOP were identified by searching electronic databases, references from relevant stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…Previous studies have shown that doxapram reduces apnea frequency and the need for invasive mechanical ventilation [4]. However, a recent systematic review, based on a small number of studies with mainly low quality of evidence, indicated that no firm conclusions can be drawn on the efficacy and safety of doxapram [7]. Furthermore, its working mechanism is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that doxapram reduces apnea frequency and the need for invasive mechanical ventilation [4]. However, a recent systematic review, based on a small number of studies with mainly low quality of evidence, indicated that no firm conclusions can be drawn on the efficacy and safety of doxapram [7]. Furthermore, its working mechanism is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some small physiological studies have shown an increase in minute ventilation and tidal volume after infusion of doxapram, but only if dosed > 1 mg/kg/h [5, 6]. However, due to concerns about the effect of doxapram on long-term outcomes of preterm infants it is used as a rescue in infants with imminent respiratory failure due to severe AOP [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, doxapram is only licensed for use in children over 12 and the efficacy of doxapram for the treatment of AOP has rarely been studied . This might be due to the fact that in the UK and USA, doxapram is only available in a solvent containing the toxic excipient benzyl alcohol, which raises concerns about toxicity, although these have not been confirmed yet .…”
Section: Discussionmentioning
confidence: 99%
“…Doxapram is off‐label for use in children and neonates, and evidence about efficacy and safety has been limited to a few small studies that have reported successful control of AOP cases that were unresponsive to methylxanthines. Other reports on doxapram therapy suggest adverse side effects, such as gastrointestinal disturbances, increased agitation, excessive crying, jitteriness, irritability , hypokalaemia , hypertension , atrioventricular heart block , higher percentages of continuous activity, more electrographic seizure activity and less sleep–wake cycling than in control groups .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the quality of evidence was also assessed for the main outcome measures using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach16 by two independent reviewers (RV and MM), as previously described 17. The following (clinical relevant) outcomes were assessed: combined outcome death or BPD, BPD, tachycardia, necrotizing enterocolitis (NEC), intraventricular haemorrhage (IVH) ≥grade 2, death or disability at 1-year CA.…”
Section: Methodsmentioning
confidence: 99%